Blautia producta displays potential probiotic properties against dextran sulfate sodium-induced colitis in mice - Bingyong Mao; Weiling Guo; Shumao Cui; Qiuxiang Zhang; Jianxin Zhao; Xin Tang; Hao Zhang (Food Science and Human Wellness)
Blautia has attracted attention because of its potential efficacy in ameliorating host energy metabolism and inflammation. This study aims to investigate the influences of Blautia producta D4 on colitis induced by dextran sulfate sodium (DSS) and to reveal the underlying mechanisms. Results showed that B. producta D4 intervention significantly relieved body weight loss, and suppressed the elevation of pro-inflammatory cytokines (including interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and interleukin-1β (IL-1β)) and excessive oxidative stress (myeloperoxidease (MPO) activity, superoxide dismutase (SOD) activity, glutathione peroxidase (GSH-Px) activity, and malondialdehyde (MDA) level) in colitis mice. Moreover, the concentrations of tight junction proteins (occludin, claudin-1, and ZO-1) related to the intestinal barrier were obviously elevated, and colitis-related TLR4/NF-κB pathway activation was remarkably inhibited after B. producta D4 intervention. The intestinal microbial disorder was evidently ameliorated by increasing the relative abundance of Clostridium sensu stricto 1, Bifidobacterium, GCA-900066225, Enterorhabdus, and reducing the relative abundance of Lachnospiraceae NK4A136 group. In conclusion, oral administration of B. producta D4 could ameliorate DSS-induced colitis by suppressing inflammatory responses, maintaining the intestinal barrier, inhibiting TLR4/NF-κB pathway, and regulating intestinal microbiota balance. These results are conducive to accelerate the development of B. producta D4 as a functional probiotic for colitis.